Restless legs syndrome in hemodialysis patients - Shahram Rafie; Majid Jafari; Mostafa Azizi; Mohammad Bahadoram; Shima Jafari (Saudi Journal of Kidney Diseases and Transplantation, 2016)
Restless legs syndrome (RLS) is a neurological disorder characterized by uncomfortable sensation of paresthesia in legs that subsequently causes involuntary and continuous movement of the lower limbs, especially at rest. Its prevalence in hemodialysis is more than that in the general population. Different risk factors have been suggested for RLS. We studied the prevalence and risk factors of RLS in 137 hemodialysis patients followed up at our center. The patients completed at least three months on dialysis and fulfilled four criteria for the diagnosis of RLS. We compared the patients with and without RLS, and the odds ratios (ORs) were estimated by the logistic regression models. The prevalence of RLS was 36.5% in the study patients. Among the variables, diabetes was the only predicting factor for the development of RLS. The diabetic patients may be afflicted with RLS 2.25 times more than the non-diabetics. Women developed severe RLS 5.23 times more than men. Neurodegeneration, decrease in dopamine level, higher total oxidant status, and neuropathy in diabetic patients may explain the RLS symptoms.